Comparison of maximal glycolytic rate from ergometer to on-water sprinting in elite canoe polo players - Meixner, Benedikt; Matzka, Manuel; Sperlich, Billy (Applied Physiology, Nutrition, and Metabolism, 2025)
Keywords: diagnostic; anaerobic metabolism; upper body; glycolysis

Evaluating the maximal rate of lactate accumulation and estimated maximal lactate steady state in cycling - Sablain, Mattice; Sperlich, Billy; Meixner, Benedikt; Caen, Kevin; Vermeire, Kobe; Boone, Jan (European Journal of Applied Physiology, 2025)
Keywords: Lactate threshold; Maximal lactate steady state; Glycolysis; Maximal rate of blood lactate accumulation; Reliability

Relationship of peak capillary blood lactate accumulation and body composition in determining the mechanical energy equivalent of lactate during sprint cycling - Meixner, Benedikt; Nusser, Valentin; Koehler, Karsten; Sablain, Mattice; Boone, Jan; Sperlich, Billy (European Journal of Applied Physiology, 2024)

Reliability of power output, maximal rate of capillary blood lactate accumulation, and phosphagen contribution time following 15-s sprint cycling in amateur cyclists - Meixner, Benedikt; Nusser, Valentin; Koehler, Karsten; Sablain, Mattice; Boone, Jan; Sperlich, Billy (Physiological Reports, 2024)

Sprint performance and the influence of body composition on power and lactate in a vLamax-test in amateur cyclists - Meixner, Benedikt; Nusser, Valentin; Koehler, Karsten; Sperlich, Billy (29th Annual Congress of the European College of Sport Science, 2024)

Supplementation of Creatine Monohydrate Improves Sprint Performance but Has no Effect on Glycolytic Contribution: A Nonrandomized, Placebo-Controlled Crossover Trial in Trained Cyclists - Meixner, Benedikt; Stegmaier, Johanna; Renner, Peter; Koehler, Karsten; Yang, Woo-Hwi; Sperlich, Billy (Current Developments in Nutrition, 2025)
Keywords: body composition; ergogenic aid; alactic; anaerobic; lactate; fat-free mass; high-intensity cycling

The effect of creatine supplementation on power output, lactate accumulation following 15 s all out sprint tests - Meixner, Benedikt; Nusser, Valentin; Koehler, Karsten; Sperlich, Billy (Science & Cycling, 2024)

Uncertainty in determining the optimal test duration for maximal rate of lactate accumulation during all‐out sprint cycle ergometry - Yang, Woo-Hwi; Meixner, Benedikt; Sperlich, Billy (European Journal of Applied Physiology, 2024)

Zone 2 Intensity: A Critical Comparison of Individual Variability in Different Submaximal Exercise Intensity Boundaries - Meixner, Benedikt; Filipas, Luca; Holmberg, Hans-Christer; Sperlich, Billy (Translational Sports Medicine, 2025)
Introduction: Endurance athletes often utilize low-intensity training, commonly defined as Zone 2 (Z2) within a five-zone intensity model, for its potential to enhance aerobic adaptations and metabolic efficiency. This study aimed at evaluating intra- and interindividual variability of commonly used Z2 intensity markers to assess their precision in reflecting physiological responses during training. Methods: Fifty cyclists (30 males and 20 females) performed both an incremental ramp and a step test in a laboratory setting, during which the power output, heart rate, blood lactate, ventilation, and substrate utilization were measured. Results: Analysis revealed substantial variability in Z2 markers, with the coefficients of variation (CV) ranging from 6% to 29% across different parameters. Ventilatory Threshold 1 (VT1) and maximal fat oxidation (FatMax) showed strong alignment, whereas fixed percentages of HRmax and blood lactate thresholds exhibited wide individual differences. Discussion: Standardized markers for Z2, such as fixed percentages of HRmax, offer practical simplicity but may inaccurately reflect metabolic responses, potentially affecting training outcomes. Given the considerable individual variability, particularly in markers with high CVs, personalized Z2 prescriptions based on physiological measurements such as VT1 and FatMax may provide a more accurate approach for aligning training intensities with metabolic demands. This variability highlights the need for individualized low-intensity training prescriptions to optimize endurance adaptations in cyclists, accommodating differences in physiological profiles and improving training specificity.
CRIS-Team Scopus Importer:2025-04-11
Keywords: aerobic exercise; exercise metabolism; moderate intensity; substrate utilization; training prescription